Measurements of differential cross sections of Higgs boson production through gluon fusion in the H → WW* → evµv final state at √s = 13 TeV with the ATLAS detector - Aad, Georges; Baltes, Lisa Marie; Bartels, Falk; Castillo, Florencia Luciana; Czurylo, Marta; Rio, Fernando del; Dittmeier, Sebastian; Dunford, Monica; Franchino, Silvia; Junkermann, Thomas; Klassen, Martin; Mkrtchyan, Tigran; et al. (The European physical journal. C, Particles and fields, 2023)
Higgs boson production via gluon-gluon fusion is measured in the WW* → evµv decay channel. The dataset utilized corresponds to an integrated luminosity of 139 fb-1 collected by the ATLAS detector from√s =13 TeV proton-proton collisions delivered by the Large Hadron Collider between 2015 and 2018. Differential cross sections are measured in a fiducial phase space restricted to the production of at most one additional jet. The results are consistent with Standard Model expectations, derived using different Monte Carlo generators.